Perilaku Konsumen dalam Pembelian Duku dan Implikasinya terhadap Pengembangan Buah Unggulan Lokal dalam Menghadapi Masyarakat Ekonomi ASEAN (MEA) - Indri Januarti; Eka Mulyana; Maryanah Hamzah (Jurnal Penyuluhan, 2021)
Product competitiveness that must be high in the MEA era does not only apply to industrial products, but also to fruit, including duku. The objectives of this study are (1)to explore consumer behavior in the duku fruit purchase decision process in the MEA era and (2)analyze consumer preferences for the fruit attributes so that it can be known what the ideal duku design is according to consumers. To explore consumer behavior used descriptive analysis, while for analyzing consumer preferences towards attributes using conjoined analysis. From the results of the study, consumer behavior through five stages, namely the introduction of needs, information search, alternative evaluation, purchase and post-purchase. From the results of the analysis, the thing that is considered most important in choosing the fruit attributes of duku is taste, seed size, price, fruit size, hardness of flesh, color of flesh, spots on the skin and skin color. Based on the results of consumer preference analysis, it can be concluded that consumers prefer duku which has the characteristics of sweetness, a small size of seeds, the price is less than IDR 8,000, the size of a large, flesh soft, clear color of flesh, spots are small and yellow skin color.